The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14051153
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Carboxymethylcellulose Biocomposite Wound-Dressings with Antimicrobial Activity

Abstract: Microbial infections associated with skin diseases are frequently investigated since they impact on the progress of pathology and healing. The present work proposes the development of freeze-dried, glutaraldehyde cross-linked, and non-cross-linked biocomposite dressings with a porous structure, which may assist the reepithelization process through the presence of collagen and carboxymethylcellulose, along with a therapeutic antimicrobial effect, due to silver nanoparticles (AgNPs) addition. Phisyco-chemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Diffraction planes of fcc Ag were evidenced from SAED patterns, which was in compliance with XRD results and previous studies [77,78]. Moreover, as the crystallite size estimated from XRD data was comparable with the particle size estimated from TEM results for all samples, we concluded that spherical monocrystalline Ag@EO NPs were successfully obtained in our study.…”
Section:  Discussionsupporting
confidence: 91%
“…Diffraction planes of fcc Ag were evidenced from SAED patterns, which was in compliance with XRD results and previous studies [77,78]. Moreover, as the crystallite size estimated from XRD data was comparable with the particle size estimated from TEM results for all samples, we concluded that spherical monocrystalline Ag@EO NPs were successfully obtained in our study.…”
Section:  Discussionsupporting
confidence: 91%
“…In this regard, numerous structures of such materials have been used. Amongst them, CMC-based hydrogels [250][251][252], films [253,254], fibers [255][256][257], wafers [258][259][260], gauzes [261,262], and nanoparticles [263][264][265] have gained much interest during the past decades.…”
Section: Tissue Engineering Wound Dressingmentioning
confidence: 99%
“…In this work, an innovative, eco-friendly hydrogel, based on a mixture of polysaccharides and clays, has been developed to locally release berberine. Thanks to its biocompatibility, hydrophilicity, biodegradability, tissue resembling, pro-haemostatic properties and low cost [12][13][14][15], the sodium salt carboxymethyl cellulose (CMCNa) was used for the development of hydrogel films using gallium (Ga 3+ ) ions as crosslinkers. This approach represents a novelty in respect to the usual-often toxic-crosslinkers, such as covalent crosslinkers (i.e., carbodiimide crosslinkers, various glycidyl ethers, etc.…”
Section: Introductionmentioning
confidence: 99%